Transparency and Accountability in the Synodal Church - Mathew Illathuparampil (Asian Horizons, 2025)
Hopes for a synodal Church are enormously rising all over the world. One expected characteristic of such a synodal Church is greater transparency and accountability. Reasons are many for the faithful to argue that the present Church is not sufficiently transparent and accountable. Given this general experience and the increasing call for transparency, this article begins exposing the concept of transparency and accountability. After having placed them in proper theological context, this article argues further that transparency is not anymore an option but a moral obligation for the Church. It is argued that transparency cannot be ensured by legal mechanisms alone, for it is based more on trust built up in the Church by participation and co-responsibility of all its members. In other words, as the Church evolves more and more synodal, it would become more and more transparent. The expected areas of transparency are pointed out in the next section. The means to ensure greater transparency are proposed in the final section.